Biotransformation of bisphenol A in vivo and in vitro by laccase-producing Trametes hirsuta La-7: Kinetics, products, and mechanisms. (15th March 2023) - Liu, Jie; Sun, Kai; Zhu, Rui; Wang, Xun; Waigi, Michael Gatheru; Li, Shunyao
Abstract: Bisphenol A (BPA) is a ubiquitous endocrine disruptor that poses adverse human health risks. Herein, biotransformation kinetics, products, and mechanisms of BPA undergoing a laccase-producing Trametes hirsuta La-7 metabolism were for the first time reported. Strain La-7 could completely biotransform ≤0.5 mmol·L −1 BPA within 6 d in vivo . Notably, its extracellular crude laccase solution (ECLS) and intracellular homogenized mycelium (HM) only required 6 h to convert 85.71% and 84.24% of 0.5 mmol·L −1 BPA in vitro, respectively. The removal of BPA was noticeably hampered by adding a cytochrome P-450 inhibitor (piperonyl butoxide) in HM, disclosing that cytochrome P-450 monooxygenase participated in BPA oxidation and metabolism. BPA intermediates were elaborately identified by high-resolution mass spectrometry (HRMS) combined with 13 C stable isotope ratios (BPA: 13 C12 -BPA = 0.25: 0.25, molar concentration). Based on the accurate molecular mass, isotope labeling difference, and relative intensity ratio of product peaks, 6 versatile metabolic mechanisms of BPA, including polymerization, hydroxylation, dehydration, bond cleavage, dehydrogenation, and carboxylation in vivo and in vitro, were confirmed. Germination index values revealed that inoculating strain La-7 in a BPA-contaminated medium presented no phytotoxicity to the germinated radish ( Raphanus sativus L.) seeds. In vivo, Mg 2+, Fe 2+, Fe 3+, and Mn 2+ were conducive to BPA removal, but Cd 2+ and Hg 2+ significantly obstructed BPA elimination. Additionally, strain La-7 also exhibited high-efficiency metabolic ability toward estrone (E1), 17 β -estradiol (E2), and 17 α -ethinylestradiol (EE2), with more than 96.13%, 96.65%, and 100% of E1, E2, and EE2 having been converted, respectively. Our findings provide an environmentally powerful laccase-producing fungus to decontaminate endocrine disruptor-contaminated water matrices by radical polymerization and oxidative decomposition. Graphical abstract: Image 1 Highlights: Laccase-producing T. hirsuta La-7 could effectively biotransform BPA in vivo and in vitro. A HRMS combined with isotope ratios was established to accurately recognize BPA intermediates. 6 versatile metabolic pathways of BPA in vivo and in vitro were for the first time supposed. Inoculating strain La-7 evaded BPA phytotoxicity to the germinated radish seeds. Strain La-7 also exhibited high-efficiency metabolic ability toward E1, E2, and EE2 in vivo.